2018
DOI: 10.15407/agrisp5.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of decreasing harmfulness of fusariosis agents in agrophytocenoses

Abstract: Infections of cultivated plants, transmitted by fusariosis agents, are among the most harmful factors for humans in grain production. Thus, there is an obvious need for effective control over harmfulness of fusariosis agents in agrophytocenoses. Summarizing scienti¿ c data on the issues of forming the strategy of decreasing harmfulness of fusariosis agents in agrocenoses. The major factors of decreasing the level of infecting cereal crops with fusarioses are genetic improvement of plants via selection of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…A wide range of studies have shown that using diverse crop rotations in which non-Fusarium host plant species precede cereal crops is an effective way of reducing the risk of Fusarium and mycotoxin contamination in cereal grains [4,6,7,10,[13][14][15]47,[52][53][54][55][56][57][58][59][60][61][62][63]. Growing non-Fusarium host crops (e.g., oilseed rape, potatoes, legumes, and field vegetables) before cereals reduces the level of Fusarium-infected crop debris, and after 2-3 years of growing a non-Fusarium host plant species, they are thought to effectively remove Fusarium pathogen inoculum from agricultural soils.…”
Section: Crop Rotationmentioning
confidence: 99%
“…A wide range of studies have shown that using diverse crop rotations in which non-Fusarium host plant species precede cereal crops is an effective way of reducing the risk of Fusarium and mycotoxin contamination in cereal grains [4,6,7,10,[13][14][15]47,[52][53][54][55][56][57][58][59][60][61][62][63]. Growing non-Fusarium host crops (e.g., oilseed rape, potatoes, legumes, and field vegetables) before cereals reduces the level of Fusarium-infected crop debris, and after 2-3 years of growing a non-Fusarium host plant species, they are thought to effectively remove Fusarium pathogen inoculum from agricultural soils.…”
Section: Crop Rotationmentioning
confidence: 99%